A Successful Pregnancy Despite the Presence of an Intrauterine Fetal Bone Fragment: A Case Report. (15th October 2019) - Petrakis, Evangelos; Chatzipapas, Ioannis; Papapanagiotou, Ioannis K.; Fotinopoulos, Panagiotis; Siemou, Panagiota; Ntzeros, Konstantinos; Loutradis, Dimitrios
Abstract : Objective . Intrauterine retention of fetal bones following a termination of a pregnancy is a rare complication. Among the few reported cases in literature, there has been no report describing the birth of a live fetus, despite the presence of an embryonic ossicle within the endometrial cavity. Case Report . A 28-year-old woman, with an obstetrical history of a miscarriage at the 19 th week of gestation, underwent a diagnostic hysteroscopy for evaluation of pelvic pain and infertility, which revealed an intrauterine embryonic ossicle. The patient did not comply with our recommendations to undergo a surgical hysteroscopy. The patient's next visit was during her 9 th week of gestation. She was followed up regularly at our Obstetrics Department. Her gestation was uneventful, while an elective caesarean section at the 39 th week of gestation was performed. Conclusion . The present clinical case has demonstrated that achieving childbearing is possible, despite the requirement of removing such bone fragments.